PEMANFAATAN TIKTOK SEBAGAI MEDIA PENGEMBANGAN USAHA MIKRO DALAM PENDIDIKAN KEWIRAUSAHAAN: STUDI MULTI-KASUS KONTEN BISNIS ONLINE - Qothrun Nada; Ferida Rahmawati; Firma Linda Aida (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2026)
This study examines TikTok as a medium for developing microenterprises within entrepreneurship education by analyzing online business content produced and used by Indonesian MSMEs. The article responds to a gap in previous discussions that tend to treat TikTok merely as a digital marketing channel, while its pedagogical value for entrepreneurial learning remains underexplored. A qualitative descriptive design was applied through a literature-based multiple-case study and digital document analysis. The cases were selected from published studies and publicly observable business content representing culinary, fashion, accessories, and mixed retail sectors. Data were analyzed using the AISAS communication model, the 7P marketing mix for live streaming commerce, the Resource-Based View, and the perspective of digital entrepreneurship competence. The findings show that TikTok can function as an experiential learning environment where students and microentrepreneurs practice opportunity recognition, content design, customer interaction, transaction management, digital analytics, and platform compliance. Short-video content mainly supports attention, interest, and search activities, whereas TikTok Live and TikTok Shop strengthen action, feedback, and post-purchase sharing. Nevertheless, sustainable benefits depend on internal capabilities, especially digital literacy, content consistency, human resource allocation, and basic legal awareness. The study proposes a learning cycle of observe, design, publish, engage, evaluate, and reflect as a practical model for integrating TikTok-based business content into entrepreneurship education.